2022
DOI: 10.3926/ic.1781
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employee empowerment on organizational performance: A mediating role of employee engagement and organisational citizenship behaviour

Abstract: Purpose:The aim of the study is to assess the mediating role of employee engagement and organisational citizenship behaviour on the relationship between employee empowerment (structural, psychological) and organisational performance in non-commercial banks in Ghana.Design/Methodology/ approach: SEM (EQS) was used to test the proposed hypothesis based on 304 employees selected from eight non-commercial banks in the Bono Region, Ghana.Findings: Organisational citizenship behaviour was a significant mediator on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Research conducted by (Afram et al, 2022) indicates a significant and beneficial relationship between employee empowerment and organizational performance. The hypothesis of this study is as follows, based on previous research: H4: Employee empowerment has a positive impact on organizational performance.…”
Section: Effect Employee Empowerment On Organizational Performancementioning
confidence: 99%
“…Research conducted by (Afram et al, 2022) indicates a significant and beneficial relationship between employee empowerment and organizational performance. The hypothesis of this study is as follows, based on previous research: H4: Employee empowerment has a positive impact on organizational performance.…”
Section: Effect Employee Empowerment On Organizational Performancementioning
confidence: 99%
“…For example, Trespalacios and Perkins (2016) found that sense of community as a proxy of workplace spirituality does not impact on performance. Afram et al (2022) also claims that empowerment as an indicator of work effectiveness does not influences performance. Another study indicated that performance impacts effectiveness (Jiang & Liu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…When individuals feel empowered to contribute their unique ideas and see the impact of their suggestions, they become more invested in their work and more likely to go the extra mile (Hoque et al, 2018). Moreover, a culture that encourages continuous learning and improvement shows that the organization values its employees' growth, fostering a sense of loyalty and commitment among team members (Afram et al, 2022). Team creativity and continuous improvement have a profound impact on sales performance.…”
Section: Introductionmentioning
confidence: 99%